Expression of E-cadherin in oesophageal carcinomas from the UK and China: disparities in prognostic significance. Issue 8 (August 1997) - Jian, W G; Darnton, S J; Jenner, K; Billingham, L J; Matthews, H R
Abstract : AIMS: To study the expression and prognostic significance of the cell adhesion molecule E-cadherin in oesophageal tumours from the UK (low risk area) and China (high risk area). METHODS: E-cadherin expression was measured immunohistochemically in resected tumours from 17 patients in the UK with adenocarcinoma, 23 patients from the UK with squamous carcinoma, and 30 patients from China with squamous carcinomas who survived for five years postoperatively and compared with similar tumours from patients in the same regions who did not survive (140 tumours in all). RESULTS: Normal squamous epithelial cells and well differentiated areas of tumours showed membranous staining for E-cadherin expression. Cytoplasmic staining, heterogeneous staining, or an absence of staining was seen in dysplastic epithelium and in less well differentiated areas of tumours. Only one of 140 primary tumours had homogeneous membranous expression. In tumours from UK patients with adenocarcinoma (p = 1.00) and from Chinese patients with squamous carcinomas (p = 0.06) there was no correlation between E-cadherin absence and non-survival. In tumours from UK patients with squamous carcinomas there was a significant correlation between absence of E-cadherin and non-survival (p = 0.009). Tumours from UK patients with squamous carcinoma who survived were significantly less likely to be E-cadherin absent than those from Chinese patients with squamous carcinomas who survived (p = 0.007). Multivariate analysis (n = 37 UK, paired data) showed that absence of E-cadherin in the primary tumour was a weak independent prognostic factor for non-survival (30% significance level; p = 0.26; odds ratio = 3.56). In UK nodal metastases there was no correlation between E-cadherin expression and survival. CONCLUSIONS: Squamous carcinomas from UK patients differed from both adenocarcinomas from UK patients and carcinomas from Chinese patients with respect to E-cadherin expression and prognostic significance. In tumours from UK patients, E-cadherin absence in the primary carcinoma (a weak independent prognostic factor) but not metastases correlated with non-survival.